'Over-researched' and 'Under-researched' refugee groups: Exploring the phenomena, causes and consequences. (6th January 2021) - Omata, Naohiko
Summary: Drawing upon my fieldwork experience in East Africa, this article sheds light on emerging phenomena of 'over-researched' and 'under-researched' refugee populations. Over the past years, I have increasingly encountered 'research fatigue' amongst certain groups of refugees who have undergone frequent studies by numerous researchers. On the other hand, I have also noticed disappointment and frustration from groups of refugees who feel that they remain 'under-studied' despite their hidden challenges and vulnerabilities. While the phenomena of over- and under-research are not new, few studies are done to compare the under- and over-studied refugees and to investigate the causes and consequences of the polarisation of research interest amongst refugee populations. This article thus aims to narrow these gaps and also explores these phenomena in relation to accountability and ethics related to forced migration scholarship. I also present practical actions toward improvement of this research polarisation.